IMPLEMENTASI KEBIJAKAN PEMBANGUNAN SUKU BADUY KABUPATEN LEBAK PROVINSI BANTEN - Sumawijaya; I Nyoman Sumaryadi; Erliana Hasan; Sampara Lukman (GoAcademica Research dan Publishing, 2020)
This research is to examine the implementation of the Baduy Tribe Development Policy, supporting and inhibiting factors in physical and non-physical development and to provide new concepts in the development of traditional primitive societies. This study uses a qualitative method. Based on the results of the research, it shows that the implementation of this policy affects the condition of the Baduy community who have been isolated and left behind because of the limitations of physical and non-physical development, starting to open up to the outside community, but changes can occur without violating the Pikukuh set by Pu'un (the traditional head) The implementation of Baduy ethnicity policy includes the content of the policy and the policy environment which includes aspects of the affected interests, types of benefits, degrees of change and program implementers. The bottom-up approach is the most appropriate to be used in efforts to tackle the development of the Baduy community, where the community is positioned as an actor (subject) development which is expected to have a positive influence on the community empowerment process itself in an effort to build independence. Synchronization of various elements plays an important role in implementing Baduy development policies. With synchronization in the implementation process, the Baduy development policy will be implemented better.